2022
DOI: 10.1039/d2ta00208f
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms of voids and pin-holes in CuSbS2 thin film synthesized by sulfurizing a co-sputtered Cu–Sb precursor

Abstract: Chalcostibite CuSbS2 is a promising alternative absorber material for thin film solar cells but the poor photovoltaic devices performance limits its wide application. In this work, one of the main...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As shown in figure 5(i), the optical bandgap of films decreased with the increasing temperature, and optical bandgaps were 2.5 eV (250 °C), 2.19 eV (300 °C), and 1.77 eV (350 °C), respectively. The difference in bandgap between the measured values and the published values [41,[48][49][50] is due to the fact that pure Cu 3 SbS 4 films were not obtained at 350 °C during the experiments. As shown in figure 2(d), the diffraction peak of the (102) CuS film is still present at 350 °C, indicating that the Cu 3 SbS 4 phase is gradually formed from the impurity phase (Cu 2−x S, Sb x S) at 250 °C-350 °C.…”
Section: Cu 3dmentioning
confidence: 69%
“…As shown in figure 5(i), the optical bandgap of films decreased with the increasing temperature, and optical bandgaps were 2.5 eV (250 °C), 2.19 eV (300 °C), and 1.77 eV (350 °C), respectively. The difference in bandgap between the measured values and the published values [41,[48][49][50] is due to the fact that pure Cu 3 SbS 4 films were not obtained at 350 °C during the experiments. As shown in figure 2(d), the diffraction peak of the (102) CuS film is still present at 350 °C, indicating that the Cu 3 SbS 4 phase is gradually formed from the impurity phase (Cu 2−x S, Sb x S) at 250 °C-350 °C.…”
Section: Cu 3dmentioning
confidence: 69%
“…In addition, PV devices that use CuSbS 2 thin films as absorbent layers have serious problems, such as poor repeatability and relatively low efficiency values (3.22%). 7,26,27 In these studies, it has been estimated that the CuSbS 2 phase has an indirect band gap with a low gap mobility, indicating that it is unlikely to achieve the desired transport properties for use in photovoltaic applications. Subsequent studies have shown that Sb rich samples of this material can lead to the desired stoichiometry and an improved performance in photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%